Remittances of guest workers to their home countries: An econometric analysis - Ursula Oser (Universität Konstanz, Forschungsschwerpunkt Internationale Arbeitsmarktforschung, 1995)
The paper presents empirical evidence on the determinants of guest workers' remittance decision. Using a West German data set, the Socio-Economic Panel (SOEP), it is shown that the intensity to remit is well explained by remigration plans,- personal characteristics, indicators for the degree of the guest worker's integration into the German economy and variables for disposable income. Furthermore, it is shown how the relative importance of specific determinants of the individual remittance decision have changed over the observation period 1984-1991.
Keywords: 330; Arbeitsmigranten; Rückwanderung; Deutschland